Peran Kepuasan Pelanggan Memediasi Pengaruh Kualitas Produk terhadap Niat Beli Ulang : (Studi pada Pelanggan Produk Fashion Merek Uniqlo di Kota Denpasar) - Ni Kadek Ari Vivekananda; Ni Made Rastini (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The increasingly competitive fashion industry requires companies to maintain product quality in order to retain customers and encourage repurchase intention. Uniqlo, as one of the global fashion brands experiencing rapid growth in Indonesia, faces challenges in maintaining consistent product quality to ensure customer satisfaction. This study aims to explain the role of customer satisfaction in mediating the effect of product quality on repurchase intention among customers of Uniqlo fashion products in Denpasar City. This study employed a quantitative approach with a causal associative design. Data were collected using a hybrid method through online questionnaires distributed via Google Forms and offline questionnaires to 140 respondents who had previously purchased Uniqlo products in Denpasar City. The data analysis technique used was Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS 4 software. The results showed that product quality has a positive and significant effect on repurchase intention, product quality has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on repurchase intention, and customer satisfaction significantly mediates the effect of product quality on repurchase intention through complementary partial mediation. The practical implication for the company is the importance of maintaining consistency and continuously improving product quality in order to create sustainable customer satisfaction and encourage repurchase intention.